HUKUM TEKNOLOGI INFORMASI TENTANG PENIPUAN TRANSAKSI JUAL BELI ONLINE - Muhammad Randy Ammar; Richardo Nezar M; Jievello Leonardo D; Raihana Nasution (JURNAL SOSIO-KOMUNIKA, 2023)
This study uses a statutory legal approach, where the level of success depends on law enforcers in handling a case in the investigative and investigative stages. The use of the law can legally ensnare perpetrators who have been proven guilty of committing a crime. This study aims to find out the legal arrangements in Indonesia for fraud in cybercrime and what regulations are the basis for law enforcement officials in efforts to deal with criminal acts of fraud in the form of online buying and selling. Cybercrime is a form of crime that arises because of the use of internet technology. The rapid development in the use of internet services invites crime to occur. With the increasing number of requests for internet access, crimes against the use of information technology are increasing following the development of the technology itself. More and more parties are harmed by the actions of the perpetrators of cybercrime if there is no law that regulates it. Prior to the enactment of the ITE Law, legal officials used the Criminal Code in dealing with cases of cyber crimes. This criminal act of fraud can be charged with Article 378 of the Criminal Code as a criminal act of fraud or Article 28 paragraph (1) of the ITE Law concerning regulations regarding the spread of false and misleading news that harms consumers. Or you can be charged based on both articles at the same time, namely, 378 of the Criminal Code in conjunction with Article 28 paragraph (1) in conjunction with Article 45 paragraph (1) of Law No. 11 of 2008 concerning fraud and/or ITE crimes.